Development of Effect Teacher Leadership Style in Special Education Integration Program (Kepimpinan Guru da/am Program Integrasi Pendidikan Khas). - See , Ching Mey

(untitled)
A descriptive study using questionnaires was conducted to assess the perception and the implementation of teacher leadership practice displayed by Integrated Special Education Program teachers in the four regions of Malaysia.